1968
DOI: 10.1017/s0031182000069341
|View full text |Cite
|
Sign up to set email alerts
|

On the bionomics ofCrepidostomum metoecus(Braun, 1900) andCrepidostomum farionis(Müller, 1784) (Trematoda: Allocreadiidae)

Abstract: The life-cycles of the two species ofCrepidostomumoccurring in a stream in North Wales are investigated. Both species share the same arthropod and definitive hosts, viz.Gammarus pulexandSalmo trutta, respectively, but have different molluscan hosts, viz.:Lymnaea peregraforC. metoecusandPisidium casertanumforC. farionis.C. metoecusandC. farionishave annual cycles, hence periodicity of occurrence in their hosts. InC. metoecusthe dynamics of occurrence in the three hosts are correlated. The inverse relationship i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
1
27
0
3
Order By: Relevance
“…Parasite transmission and mayfly emergence that occurs in June and July in the St. Marys River begins during a period of rapidly rising water temperatures. Other researchers have observed similar associations between parasite and host lifecycles, parasite transmission, and water temperature (Awachie, 1968;Hazen & Esch, 1977;Esch & Hazen, 1982).…”
Section: Seasonal Abundancementioning
confidence: 58%
See 1 more Smart Citation
“…Parasite transmission and mayfly emergence that occurs in June and July in the St. Marys River begins during a period of rapidly rising water temperatures. Other researchers have observed similar associations between parasite and host lifecycles, parasite transmission, and water temperature (Awachie, 1968;Hazen & Esch, 1977;Esch & Hazen, 1982).…”
Section: Seasonal Abundancementioning
confidence: 58%
“…Various studies have suggested that metacercariae may impair body functions and cause non-lethal impacts to mayfly nymphs through decreased proteins, muscle, fat reserves, nerve ganglia, and gonadal tissues which could contribute to retarded growth, declined health, and increase mortality by other factors (Awachie, 1968;Olsen, 1974;Chambers et al, 1975;Knowles & Hall, 1976;Hominick & Welch, 1980;Moravec, 1982). Chambers et al, (1975) found substantial reductions in hemolymph proteins in heavily infected nymphs with metacercarial intensities ranging between 16 and 116 per nymph.…”
Section: Impacts Of Parasitismmentioning
confidence: 99%
“…Many studies already listed the parasitic trout species, C. metoecus, in different European countries and particularly in Ireland (Holland & Kennedy, 1997), England, Sweden (Corbett, 1955), Poland or Czech Republic (Slusarski, 1958) and North Eastern Finland (Rahkonen & Valtonen, 1989). Considering its important geographical distribution (Chubb, 1979), this parasite must have diverse intermediate hosts (Awachie, 1968) according to the biotope which its definitive host colonizes. The presence of the nematode, R. gnedini is well known in Salmo trutta.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies already listed these parasitic species of trout in different European countries and particularly in Ireland [12], England, Sweden [8], Poland or Czech republic [21]. Considering its important geographical distribution [6], this parasite must have diverse intermediate hosts [2] according to the biotope which its definitive host colonizes. Presence of the nematode, R. gnedini is well known in Salmo trutta.…”
Section: A Trematodamentioning
confidence: 99%